1959
DOI: 10.1161/01.cir.19.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol in Man: Diet Fat and Intrinsic Responsiveness

Abstract: Data obtained froni a nutaiber of dietary experiments in mtm yield a formuht by which the responlses in serumI cholesterol to changes in diet can be predicted. In this paiiel. the reliability of this foralula is tested and the effects of various types of fatty acids Onl seruill cholesterol are investigated.THE serum cholesterol concentration in mani is strongly influenced by both the amount aiid kind of fat in the diet and it is necessary to differentiate between at least 3 classes of fatty aci(ls, saturatedl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(26 citation statements)
references
References 19 publications
(2 reference statements)
0
25
0
1
Order By: Relevance
“…7 These conclusions were supported by small short-term human feeding studies designed to show that replacement of carbohydrate or polyunsaturated fatty acids (PUFAs) with saturated fatty acids (SFAs) increased total cholesterol. 8 A growing evidence base that includes millions of participants who have provided detailed dietary and lifestyle data and biological specimens has shaped our understanding of biological pathways for micronutrient and macronutrient metabolism and their effects on disease. Findings from these efforts serve as the foundation for the evolution of contemporary dietary guidelines, 9 which are refined as new technologies and methods permit ever more rigorous standards for defining optimal nutritional guidelines.…”
Section: Nutritional Epidemiologymentioning
confidence: 99%
“…7 These conclusions were supported by small short-term human feeding studies designed to show that replacement of carbohydrate or polyunsaturated fatty acids (PUFAs) with saturated fatty acids (SFAs) increased total cholesterol. 8 A growing evidence base that includes millions of participants who have provided detailed dietary and lifestyle data and biological specimens has shaped our understanding of biological pathways for micronutrient and macronutrient metabolism and their effects on disease. Findings from these efforts serve as the foundation for the evolution of contemporary dietary guidelines, 9 which are refined as new technologies and methods permit ever more rigorous standards for defining optimal nutritional guidelines.…”
Section: Nutritional Epidemiologymentioning
confidence: 99%
“…The significantly better lowering effect on serum total and LDL cholesterol of the diet using corn oil as the predominant fat (ta ble II) bears out the initial hypothesis of the experiment which was based on the observa tions of other investigators [12,13]. A differ ence of 6.8% in the concentration of serum cholesterol may seem small and of little prac tical consequence.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, the change in endogenous sterol excretion appeared to depend mainly on the magni tude of change in serum cholesterol, and not on the type of fat used. It has been suggested that the higher content of tocopherols and ubiquinones in germ oils may lower serum cholesterol in addition to the effect of the fatty acids [12,13,30,31], It is conceivable that these compounds could enhance the ac tion of polyunsaturated fatty acids in the body by protecting them against oxidation [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary effects on LDL were reviewed by Grundy. 21 There is now evidence which suggests that HDL cholesterol, previously thought to be unaffected by diet, 22 may be influenced along with LDL cholesterol by some dietary components.…”
Section: Response Of High Density Lipoprotein Cholesterol To Dietary mentioning
confidence: 99%